Cognitive impairment and self-reported health outcomes among older adults: Longitudinal evidence from Australia - Rezwanul Haque; Khorshed Alam; Jeff Gow; Christine Neville; Syed Afroz Keramat (Acta Psychologica)
Background: Australia's population is ageing, with forecasts indicating that individuals aged 65 years and over will account for >20 % of the total population by 2066. Ageing is strongly linked with a significant decrease in cognitive capabilities. This study aimed to explore the association between cognitive impairment and four types of health outcomes among older Australians. Methods: Data used for this study was collected from the Household, Income and Labour Dynamics in Australia (HILDA) Survey. The final analysis consisted of 11,146 person-year observations from 7035 unique individuals from Wave 2012 and Wave 2016, respectively. A longitudinal random-effects generalised least squares, and ordered logistic regression were used to analyse the association between cognitive impairment and health outcomes. Results: The study results suggest that cognitive impairment was negatively associated with general health, mental health, self-assessed health and health satisfaction. Older Australians with cognitive impairment scored lower on general health (β = −2.82, SE = 0.56), mental health (β = −2.93, SE = 0.53), self-assessed health (β = − 0.75, SE = 0.10), and health satisfaction (β = −0.19, SE = 0.09) compared to the counterparts without cognitive impairment. The heterogeneous results also showed cognitive impairment was associated with poor health outcomes across age groups. Conclusion: This study found evidence that cognitive impairment is associated with poor health outcomes. To enhance the physical and mental health and well-being of older adults, the community, government and non-government organizations, and other stakeholders should prioritize routine healthcare prevention, targeted interventions, and treatment practices, particularly for individuals with or at risk of cognitive impairment.